Republic of Djibouti : Education Strategy Note - World Bank (Washington, DC, 2013)
This strategy note highlights issues derived from the preparation of the Djibouti School Access and Improvement Project, on the overall strategy of the education sector reforms, and long-term economic reforms. It reviews the country's education indicators - among the lowest in the world - where primary gross enrollment is under forty percent, and basic education enrollment, under twenty nine percent. Djibouti's curriculum is mainly based on the French education system, barely relevant to the country's needs. To this end, the Government established a National Education Forum, which recommended changes in the education law, which were codified into a new law, adopted in August 2000. Educational restructuring took place, moving from a six-year compulsory primary school system, to a nine-year compulsory basic education system (consolidating primary, and basic education), to meet the target set for basic education for all. However, the education and training system faces serious issues, namely access to, and equity of education; weak quality of learning due to insufficient teachers, and archaic pedagogic methods; high repetition and drop-out rates, due to competitive entrance examinations, and/or social pressures; and, insufficient Government resources to increase access, or improve quality. Recommendations suggest to conduct studies on factors affecting family incentives to foster school enrollment, particularly for girls' education, and those affecting quality of education, and, to review adaptability of curricula to the local context, social demands for higher education, and gender equity issues, in addition to financing options, in particular recurrent cost issues, with a focus on the role of the private sector.